2020
DOI: 10.1096/fj.202001340r
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation‐dependent osterix degradation negatively regulates osteoblast differentiation

Abstract: Proteasome inhibitors exert an anabolic effect on bone formation with elevated levels of osteoblast markers. These findings suggest the important role of the proteasomal degradation of osteogenic regulators, while the underlying molecular mechanisms are not fully understood. Here, we report that the proteasome inhibitors bortezomib and ixazomib markedly increased protein levels of the osteoblastic key transcription factor osterix/Sp7 (Osx). Furthermore, we revealed that Osx was targeted by p38 and Fbw7 for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…To capture the early molecular events in the progression of CKD-MBD we examined pathways associated with bone remodeling at the gene expression level. In parallel with the bone histomorphometric alterations in Nx2 and Nx6, we found the down-regulation of gene expression profile related to osteoblastogenesis (Sp7 [28], Ctnnb1 [29], Bmp4 [30]), and Pi transport and sensing (Slc20a1, Slc20a2, Xpr1, Ankh, Fgfr2, Mapk1, Mapk3 [31,32]). Contrariwise, there were differences neither in osteoclast number nor in osteoclast regulatory genes expression (Tnfrsf11B, Tnfsf11, Lgr4 [9]) between experimental groups and controls.…”
Section: Discussionsupporting
confidence: 54%
“…To capture the early molecular events in the progression of CKD-MBD we examined pathways associated with bone remodeling at the gene expression level. In parallel with the bone histomorphometric alterations in Nx2 and Nx6, we found the down-regulation of gene expression profile related to osteoblastogenesis (Sp7 [28], Ctnnb1 [29], Bmp4 [30]), and Pi transport and sensing (Slc20a1, Slc20a2, Xpr1, Ankh, Fgfr2, Mapk1, Mapk3 [31,32]). Contrariwise, there were differences neither in osteoclast number nor in osteoclast regulatory genes expression (Tnfrsf11B, Tnfsf11, Lgr4 [9]) between experimental groups and controls.…”
Section: Discussionsupporting
confidence: 54%
“…Another report showed that phosphorylation of Sp7 at Ser-73 and Ser-77 is necessary for its interaction with Fbw7 (F-box/WD repeat-containing protein 7), which works as a receptor subunit of the Skp1-Cullin1-F-box-protein (SCF) Fbw7 E3 ligase complex; Fbw7-targeted Sp7 undergoes ubiquitination and subsequent degradation [ 60 ]. Thus, p38-mediated phosphorylation directs Sp7 to degradation in this context.…”
Section: Post-translational Regulation Of Sp7 Activitiesmentioning
confidence: 99%
“…S-phase kinase associated protein 2 of the Skp-Cullin-F-box family negatively regulates osteogenic differentiation by targeting RUNX2 degradation (Thacker et al, 2016). F-box/WD repeatcontaining protein 7, another component of the Skp-Cullin-Fbox ubiquitin ligase complex, has been shown to negatively regulate osterix protein stability and osteoblast differentiation (Hoshikawa et al, 2020).…”
Section: The U-box Domain Familymentioning
confidence: 99%